IRT analyses of the Swedish Dark Triad Dirty Dozen. Issue 3 (March 2018) - Garcia, Danilo; Persson, Björn N.; Al Nima, Ali; Brulin, Joel Gruneau; Rapp-Ricciardi, Max; Kajonius, Petri J.
Abstract: Background: The Dark Triad (i.e., Machiavellianism, narcissism, and psychopathy) can be captured quickly with 12 items using the Dark Triad Dirty Dozen (Jonason and Webster, 2010). Previous Item Response Theory (IRT) analyses of the original English Dark Triad Dirty Dozen have shown that all three subscales adequately tap into the dark domains of personality. The aim of the present study was to analyze the Swedish version of the Dark Triad Dirty Dozen using IRT. Method: 570 individuals ( n males = 326, n females = 242, and 2 unreported), including university students and white-collar workers with an age range between 19 and 65 years, responded to the Swedish version of the Dark Triad Dirty Dozen (Garcia et al., 2017a, b ). Results: Contrary to previous research, we found that the narcissism scale provided most information, followed by psychopathy, and finally Machiavellianism. Moreover, the psychopathy scale required a higher level of the latent trait for endorsement of its items than the narcissism and Machiavellianism scales. Overall, all items provided reasonable amounts of information and are thus effective for discriminating between individuals. The mean item discriminations (alphas) were 1.92 for Machiavellianism, 2.31 for narcissism, and 1.99 for psychopathy. Conclusion: This is the first study to provide IRT analyses of the Swedish version of the Dark Triad Dirty Dozen. Our findings add to a growing literature on the Dark Triad Dirty Dozen scale in different cultures and highlight psychometric characteristics, which can be used for comparative studies. Items tapping into psychopathy showed higher thresholds for endorsement than the other two scales. Importantly, the narcissism scale seems to provide more information about a lack of narcissism, perhaps mirroring cultural conditions.